Usual nutrient intakes of US infants and toddlers generally meet or exceed Dietary Reference Intakes: findings from NHANES 2009–2012. Issue 4 (14th September 2016) - Ahluwalia, Namanjeet; Herrick, Kirsten A; Rossen, Lauren M; Rhodes, Donna; Kit, Brian; Moshfegh, Alanna; Dodd, Kevin W
ABSTRACT: Background: To our knowledge, few studies have described the usual nutrient intakes of US children aged <2 y or assessed the nutrient adequacy of their diets relative to the recommended Dietary Reference Intakes (DRIs). Objective: We estimated the usual nutrient intake of US children aged 6–23 mo examined in NHANES 2009–2012 and compared them to age-specific DRIs as applicable. Design: Dietary intake was assessed with two 24-h recalls for infants aged 6–11 mo ( n = 381) and toddlers aged 12–23 mo ( n = 516) with the use of the USDA's Automated Multiple-Pass Method. Estimates of usual nutrient intakes from food and beverages were obtained with the use of the National Cancer Institute method. The proportions of children with intakes below and above the DRI were also estimated. Results: The estimated usual intakes of infants were adequate for most nutrients; however, 10% had an iron intake below the Estimated Average Requirement (EAR), and only 21% had a vitamin D intake that met or exceeded the recommended Adequate Intake (AI). More nutrient inadequacies were noted among toddlers; 1 in 4 had a lower-than-recommended fat intake (percentage of energy), and most had intakes that were below the EAR for vitamins E (82%) and D (74%). Few toddlers (<1%) met or exceeded the AI for fiber and potassium. In contrast, 1 in 2 had sodium intakes that exceeded the Tolerable Upper Intake Level (UL); ≥16% and 41% of the children had excessive intakes (greater than the ULs) of vitamin A and zinc, respectively. Conclusions: The estimated usual intakes of infants were adequate for most nutrients. Most toddlers were at risk for inadequate intakes of vitamins D and E and had diets low in fiber and potassium. The sources contributing to excessive intakes of vitamin A and zinc among infants and toddlers may need further evaluation.